Exploring transcriptomic databases to identify and experimentally validate tissue-specific consensus reference gene for gene expression normalization in BALB/c mice acutely exposed to 2,3,7,8-Tetrachlorodibenzo-p-dioxin - Nour Hammoudeh; Reem Hasan; Mohammad Deeb; Zuher Radwan; Omar Ayoubi; Roaa Alendary; Mouayad Youssef; Abdulfattah Kazan; Rasil Alsahli; Walaa Faiad; Nour Aldeli; Abdulsamie Hanano (Current Research in Toxicology)
2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) is a toxic compound affecting organs like the liver, kidney, lung, and reproductive systems in mammals. This study outlines a strategy for choosing appropriate HKGs for tissue-specific gene expression analysis in TCDD toxicity, including four steps: i) identifying candidate HKGs from literature and databases; ii) defining primers from literature or designing new ones; iii) validating primer efficiency and specificity; iv) experimentally assessing candidate HKGs’ stability in various tissues of TCDD-exposed mice.Based on this strategy, a total of 40 potential HKGs was selected, further filtered based on their database sources and ranked according to their frequency of use or expression stability. Ultimately, we identified a final set of 15 HKGs (Rps18, Calr, Polr2b, Brms1l, P4hb, Esd, Hdgf, Gapdh, Mlec, Tbp, Rn18s, Sdha, B2m, Actr3 and Actb) with typical efficiencies for further evaluation. Then, the stability of the selected HKGs was determined in the liver, kidney, lung, ovary and testis of TCDD-exposed mouse compared to the control group using the [log (2ΔCt)] and statistically analyzed using Pearson correlation coefficient (r) by BestKeeper algorithm. Our data analysis revealed that Actb, Rps18, and Polr2b were the most stable HKGs for normalizing gene expression in the liver, while Sdha, Actb, and Gapdh were suitable for kidney tissue. In the lung, Tbp, Sdha, and Rps18 showed stability, while Tbp, B2m, and Actb were most stable in ovary. Lastly, Actb, B2m, and Tbp were accurately stable in the testis of TCDD-exposed mice. Our study identifies stable HKGs, improving TCDD toxicity research accuracy and reliability.